Worn out how our clothes cover up fashion's sins - Hardy, Alyssa (Tantor Media, Inc., 2023)
Worn Out examines the underside of our historic clothing binge and the fashion industry's fall from grace. Former InStyle senior news editor and seasoned journalist Alyssa Hardy's riveting work explores the lives of the millions of garment workers-mostly women of color-who toil in the fashion industry around the world-from LA-based sweatshop employees who experience sexual abuse while stitching clothes for H & M, Fashion Nova, and Levi's to "homeworkers" in Indonesia who are unknowingly given carcinogenic materials to work with. Worn Out exposes the complicity of celebrities whose endorsements obscure the exploitation behind marquee brands and also includes interviews with designers such as Mara Hoffman, whose business models are based on ethical production standards. Like many of us, Hardy believes in the personal, political, and cultural place fashion has in our lives, from seed to sew to closet, and that it is still okay to indulge in its glitz and glamour. But the time has come, she argues, to force real change on an industry that prefers to keep its dark side behind the runway curtain. The perfect book for people who are passionate about clothing and style, Worn Out seeks to engage in a real conversation about who gets harmed by fast fashion-and offers meaningful solutions for change
Online resource; title from title details screen (O'Reilly, viewed March 7, 2023)
Keywords: Clothing trade -- Moral and ethical aspects; Clothing workers -- Abuse of; Work environment; Consumption (Economics); Social responsibility of business; Fashion design -- Environmental aspects; Travailleurs du vêtement; Violence envers; Entreprises; Responsabilité sociale; Clothing trade; Moral and ethical aspects; Audiobooks; Livres audio